Evaluation of postural sway and impact forces during ingress and egress of scissor lifts at elevations. (November 2017) - Pan, Christopher S.; Chiou, Sharon S.; Kau, Tsui-Ying; Wimer, Bryan M.; Ning, Xiaopeng; Keane, Paul
Abstract: Workers are at risk when entering (ingress) or exiting (egress) elevated scissor lifts. In this study, we recorded ground impact forces and postural sway from 22 construction workers while they performed ingress and egress between a scissor lift and an adjacent work surface with varying conditions: lift opening designs, horizontal and vertical gaps, and sloped work surfaces. We observed higher peak ground shear forces when using a bar-and-chain opening, with larger horizontal gap, with the lift surface more than 0.2 m below the work surface, and presence of a sloped (26°) work surface. Similar trends were observed for postural sway, except that the influence of vertical distance was not significant. To reduce slip/trip/fall risk and postural sway of workers while ingress or egress of an elevated scissor lift, we suggest scissor lifts be equipped with a gate-type opening instead of a bar-and-chain design. We also suggest the lift surface be placed no more than 0.2 m lower than the work surface and the horizontal gap between lift and work surfaces be as small as possible. Selecting a non-sloped surface to ingress or egress a scissor lift is also preferred to reduce risk. Highlights: This study quantified ground impact forces and postural sway during ingress and egress of scissor lifts. Scissor lifts should have gates in preference to bar and chain openings. The adjacent work surface should be non-sloped during ingress and egress. The lift platform surface should be less than 0.2 m (8 inches) lower than the landing surface. The horizontal distance between a lift platform surface and the adjacent work surface should be less than 0.35 m (14 inches).